Lyotard's subline : its manifestation in the musical aesthetic of Toru Takemitsu and Leo Brouwer - Du Plessis, Harm (College of Music, 2016)
The research question stems from a desire to discover what makes the guitar music of Leo Brouwer and Toru Takemitsu so conducive to aesthetic investigation, from the viewpoint of both a listener and performer of their works. The research approach is that of viewing their music through a philosophical lens provided by the notions and attitudes of postmodernism, especially through the aesthetic writings of Jean François Lyotard. Instead of embarking on an analytical investigation in order to prove the aesthetic elements perceived in the music, existing analytical research is consulted and conclusions drawn from this material as it relates to the philosophical ideas of the dissertation .The research question answered is whether there is an aesthetic common ground between Brouwer and Takemitsu that can be linked to the presence of the traditional aesthetic principles of their respective native countries in their guitar compositions. The presence of such aesthetic qualities is indeed perceptible in their music and it is the investigative aim of the dissertation to highlight these qualities as they relate to postmodern notions of time and existence. The aesthetic theory of the sublime as relayed by Lyotard functions as the philosophical premise of the dissertation. The temporal quality that Lyotard observes in the sublime is of particular importance in the selection of this philosopher's work as a theoretical framework. It will be shown that the temporal aspect which Lyotard identifies as an integral part of the sublime aesthetic is what provides the common ground between the musical of the two composers' works. The dissertation proceeds in the first chapter to explain some of the important notions of postmodernism, as they relate to the current topic, concerning the temporal aspect of human experience, in the study of history and from a philosophical view point. This leads to the ideas about temporality as an important aspect of the aesthetic of the sublime as posited by Lyotard in the second part of the first chapter. In this part of the text, reference is made to the composers Brouwer and Takemitsu in order to situate their musical philosophies and aesthetics in the philosophical framework that is provided in this chapter. A bridge between the philosophical framework is provided by devoting the second chapter to an investigation into the ideas by Jonathan D. Kramer about the temporal aspect of music. This provides a link to Lyotard's observation of the temporal aspect of the sublime.